Nations and empires - Palmer, Alan. (New York : Newsweek Books, 1974)
Traces milestones in history from the Crimean War of 1854 to the publication of Sigmund Freud's treatise on dreams in 1900.
Together with Age of optimism (published in 1974) forms a rev. and expanded ed. of Age of optimism, published in 1970.
Includes index.
2.
Keywords: History, Modern -- 19th century